Religion & Feminism: Inheritance Law in the Perspective of Gender Equality - Abdul Halim; Muzakkir Fuad; Darmadi Darmadi; Cindenia Puspasari (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2025)
Feminism is now attracting the attention of Muslims as a result of the influence of globalization. This includes disturbing inheritance law issues for women. The purpose of writing this article is to describe the problems of inheritance law for women from Amina Wadud's perspective and how Islam explains it in detail. The method used is literature study. The results of this research explain that in Islam, women are positioned as noble and empowered creatures. The Prophet Muhammad SAW taught to honor mothers three times before fathers. Women who were once considered insignificant are now respected. Islamic inheritance law emphasizes fairness between men and women